Eliciting Probabilistic Expectations with Visual Aids in Developing Countries: How Sensitive Are Answers to Variations in Elicitation Design? - Delavande, Adeline; Gine, Xavier; McKenzie, David (2012)
Eliciting subjective probability distributions in developing countries is often based on visual aids such as beans to represent probabilities and intervals on a sheet of paper to represent the support. We conduct an experiment in India which tests the sensitivity of elicited expectations to variations in three facets of the elicitation methodology: the number of beans, the design of the support (predetermined or self-anchored), and the ordering of questions. Our results show remarkable robustness to variations in elicitation design. Nevertheless, the added precision offered by using more beans and a larger number of intervals with a predetermined support improves accuracy.